Holter monitoring of ventricular arrhythmias in a randomised, controlled study of intravenous streptokinase in acute myocardial infarction. Issue 1 (January 1991) - Alexopoulos, D; Collins, R; Adamopoulos, S; Peto, R; Sleight, P
Abstract : The occurrence of ventricular arrhythmias attributed to streptokinase treatment in acute myocardial infarction is not well defined. Holter monitoring was performed for 24 hours in 81 patients with suspected acute myocardial infarction randomised in a ratio of 2:1 to intravenous streptokinase 1.5 x 10(6) IU (n = 55) or placebo infusion (n = 26) 6.7 hours (mean) after the onset of symptoms. No episodes of ventricular fibrillation were recorded. For the whole 24 hour period and during the first three hours after the start of treatment the incidence and frequency of ventricular arrhythmias were similar in the patients randomised to streptokinase and to placebo. But when the results in patients randomised "early" after the onset of symptoms of suspected acute myocardial infarction were analysed separately the frequency of abnormal complexes, pairs, runs, and repetitive arrhythmias seemed to be higher in patients allocated to streptokinase. This may reflect arrhythmias associated with reperfusion.